Image processing for geotechnical laboratory measurements - Uy, Erica Elice S. (Animo Repository, 2016)
This research is an effort to apply image processing techniques for non-contact determination of 2D and 3D displacements of specimens in a triaxial apparatus. For the 2D measurement, a calibration procedure is applied to correct image distortions before the positions of interested points are tracked by the pyramidal optical flow algorithm (Lucas and Kanade, 1981). By considering the change of position, the displacement of an interested point can be determined. The results are compared with the measurements obtained from LVDTs and are well agreed. For 3D measurement, calibration, rectification, correspondence and 3D re-projection are performed. It is verified by an isotropic compression test of a cylindrical sponge in a triaxial apparatus. The estimated displacement and discharge of water are compared with the measured ones and are well agreed. The repeatability and resolution of the developed system are found to be in the order of 0.006 cm and 0.004 cm, respectively. © 2015, Int. J. of GEOMATE. All rights reserved.